International Short Term Capital Movements: A Distributed Lag Model of Speculation in Foreign Exchange - Arndt, Sven W. (Econometrica, 1968)
The role of speculative short term capital movements in balance of payments adjustment and in exchange market stability is examined. A theory of speculative behavior with a distributed lag model of expectation formation at its core is developed and empirically tested using the Canadian data for the period 1952-1960. Tests of an alternative but generically similar specification of the model are also presented and discussed.